2018
DOI: 10.1038/s41598-018-25763-4
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic effect of renalase and chronic kidney disease on endothelin-1 in patients with coronary artery disease ‒ a cross-sectional study

Abstract: Endothelin-1 (ET-1) is associated with endothelial dysfunction and vasoconstriction. Increased circulating ET-1 levels are associated with long-term cardiovascular mortality. Renalase, released from kidney, metabolizes catecholamines and regulates blood pressure. An increase in circulating renalase levels has been reported in patients with chronic kidney disease (CKD) and is associated with coronary artery disease (CAD). We hypothesized the existence of a synergistic effect of serum renalase levels and CKD on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
10
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 51 publications
2
10
0
Order By: Relevance
“…The copyright holder for this this version posted September 16, 2021. ; https://doi.org/10.1101/2021.09.13.21263340 doi: medRxiv preprint interaction showed enrichment of genes in the signaling pathways of Rho GTPase small molecules, axon guidance, actin skeleton, VEGFA-NRP1 induced angiogenesis, and the endothelin-1 pathway. Identification of the endothlin-1 41 and TGFB1 pathways in our study is supported by prior literature on the role of these pathways in DKD susceptibility [42][43][44][45][46][47][48][49][50][51][52][53] . The Gas6-AKT pathway was shown to be involved in mesangial hypertrophy in rat models of DKD 54,55 .…”
Section: Discussionsupporting
confidence: 88%
“…The copyright holder for this this version posted September 16, 2021. ; https://doi.org/10.1101/2021.09.13.21263340 doi: medRxiv preprint interaction showed enrichment of genes in the signaling pathways of Rho GTPase small molecules, axon guidance, actin skeleton, VEGFA-NRP1 induced angiogenesis, and the endothelin-1 pathway. Identification of the endothlin-1 41 and TGFB1 pathways in our study is supported by prior literature on the role of these pathways in DKD susceptibility [42][43][44][45][46][47][48][49][50][51][52][53] . The Gas6-AKT pathway was shown to be involved in mesangial hypertrophy in rat models of DKD 54,55 .…”
Section: Discussionsupporting
confidence: 88%
“…The lack of association of the studied polymorphism with diabetic nephropathy is difficult to explain in the light of the links between renalase and kidney disease widely described in the literature. Concentrations of renalase in serum are significantly higher in patients with chronic kidney disease (CKD) than in control group and are elevated in the increasing stage of renal failure [31][32][33]. Zbroch et al described a significant inverse correlation between the serum renalase and residual renal function [34].…”
Section: Discussionmentioning
confidence: 99%
“…Li et al have indicated increased renalase serum levels in CKD patients, which correlated with increased levels of endotelin, a hormone involved in pathogenesis of cardiovascular diseases [ 27 ].…”
Section: Discussionmentioning
confidence: 99%